Historical Linguistics: Diachronic Evolution of the Arabic Language - Kusuma Dewi, Metha; Anshori, Moh; Ihsan, Wildanul (STAINI Press, 2025)
Arabic undergoes significant phonological, morphological, semantic, and syntactic changes over time, from the Jahiliyyah era to modern times. This study aims to explain the development and changes of Arabic based on the historical linguistic approach and analyze the integration of the historical approach in Arabic language learning which is more contextual and reflective. The method used is a literature study with a qualitative approach, supported by field data from madrasah. The results show that the historical approach provides a more comprehensive understanding of the dynamics of the Arabic language. In addition, the integration of language history in learning is proven to increase students' interest, morphological understanding, and critical thinking skills. Thus, this approach can be an effective strategy in learning Arabic that is not only normative, but also socially and historically meaningful.